2011
DOI: 10.1103/physreva.83.014701
|View full text |Cite
|
Sign up to set email alerts
|

State-selective electron capture inHe32+

Abstract: In this work we have measured single-electron capture in collisions of 3 He 2+ projectiles incident on a helium target for energies of 13.3-100 keV/amu with the cold-target recoil-ion momentum spectroscopy setup implemented at the Centro Atómico Bariloche. State-selective single-capture cross sections were measured as a function of the impact energy. They were found to agree with previous existing data from the Frankfurt group, starting at the impact energy of 60 keV/amu; as well as with recent data, at 7.5 ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Our calculations are performed in the energy range of 0.01 < E < 17.5 keV/u, in which the ionization cross sections are less than 20% of charge exchange results [8]. For energies larger than 5 keV/u, the present results agree well with the experimental measurements [7,8,13] and other theoretical results [20][21][22][23][24]. All these results increase with increasing the energy up to 30 keV/u.…”
Section: Total Sct Cross Sectionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our calculations are performed in the energy range of 0.01 < E < 17.5 keV/u, in which the ionization cross sections are less than 20% of charge exchange results [8]. For energies larger than 5 keV/u, the present results agree well with the experimental measurements [7,8,13] and other theoretical results [20][21][22][23][24]. All these results increase with increasing the energy up to 30 keV/u.…”
Section: Total Sct Cross Sectionsupporting
confidence: 85%
“…The present total SCT cross section that includes both the single capture and the transfer excitation cross sections (processes (1a) and (1b)) are shown in figure 4. In the same figure, the experimental results of Afrosimov et al [6], Dubois [7], Shah et al [8], Kusakabe et al [9], Okuno et al [11], Alessi et al [13], Mawhorter et al [14] and B-MD [12], as well as the results of theoretical calculations of Harel and Salin [20] obtained with the perturbed stationary state (PSS), the semiclassical MOCC (SCMOCC) results of Kimura [21], the AOCC results of Gramlich et al [22], the 2e-AOCC results of Fristch [23] and the SCMOCC results of Chaudhuri et al [24] are also shown. Our calculations are performed in the energy range of 0.01 < E < 17.5 keV/u, in which the ionization cross sections are less than 20% of charge exchange results [8].…”
Section: Total Sct Cross Sectionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is worth noting that this technique has not only been applied to the electron collisions field but in ion-impact and photonimpact studies as well [4][5][6][7][8][9]. Different laboratories worldwide adopted the technique since then [10][11][12][13]. These operating setups gave rise to large sets of data that have been useful to benchmark the existing theoretical models in different collisional processes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations in the experimental setup (only low-energy emitted electrons are detected to avoid prohibitive extraction fields), a vast amount of data has been obtained for a large variety of collision systems. More recent works have been realized in ion-atom [13,14,15,16], ion-molecule [17,18,19,20,21], and ion-cluster [22] collisions.…”
Section: Introductionmentioning
confidence: 99%